Fluorescent silver quantum cluster fluorophosphate glass and preparation method and application thereof

By constructing a molecular-grade cage structure and a high oxidation/reduction potential system in fluorophosphate glass, combined with the introduction of negatively charged tetrahedral units, the stability and uniform distribution of fluorescent silver quantum clusters in fluorophosphate glass are solved, and efficient optical storage effect is achieved.

CN116199420BActive Publication Date: 2025-04-08ZHEJIANG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310037937.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-10
Publication Date
2025-04-08
Estimated Expiration
2043-01-10

AI Technical Summary

Technical Problem

Prior Art In heavily doped silver fluorophosphate femtosecond laser glass, there are problems with the stability and uniform distribution of fluorescent silver quantum clusters [Agm]x+, resulting in fluorescence inactivation and poor chemical stability of glass.

Method used

By constructing a molecular-grade cage structure and a high oxidation/reduction potential glass system, combined with a low polarization fluorophosphate system, negatively charged tetrahedral units such as [AlO4], [MgO4] and [ZnO4] are introduced to promote uniform distribution of Ag+ ions and inhibit excessive aggregation and inactivation of [Agm]x+ quantum clusters.

Benefits of technology

The stability and uniform distribution of fluorescent silver quantum cluster [Agm]x+ is achieved, the chemical stability and optical performance of the glass are improved, and the optical storage capacity is equipped with ultra-large capacity, high density and long-life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116199420B_ABST
    Figure CN116199420B_ABST
Patent Text Reader

Abstract

The invention discloses a fluorescent silver quantum cluster fluorophosphate glass and a preparation method thereof. The components thereof are as follows in molar percentage: [SiO4] is 10-20%; [Al(O,F) x ], (4≤x≤6) is 20~25%; [P(O,F) y ], (4≤y≤6) is 40-50%; [Mg(O,F) z ], (4≤z≤6) is 0~14%; [Zn(O,F) w ], (4≤w≤6) is 0-14%; Ag is 1-5%; F / O is 4-10%. The fluorescent glass is prepared by high-temperature melting and laser treatment in two steps, and has a low laser damage threshold and high chemical stability. The present invention develops a fluorescent silver quantum cluster fluorophosphate glass with high fluorescence efficiency and good chemical stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of glass manufacturing, and in particular relates to a fluorescent silver quantum cluster fluorophosphate glass and a preparation method and application thereof. Background Art

[0002] With the popularization of 5G communication technology, mankind is entering an era of intelligent interconnected big data. According to the International Data Corporation (IDC), by 2025, the world will generate a total of 175ZB of data that year. Whether it is magnetic, electrical, or optical storage, there are problems with low storage density, high maintenance costs, and short storage life. The massive data generated by the explosive growth will bring serious problems such as power consumption and space occupation. Therefore, the development of high-density and high-reliability new information storage technology is imminent. Recently, the rapid development of femtosecond laser technology is expected to cleverly solve the contradiction between the photosensitivity required for high-speed reading and writing of large-capacity optical storage materials and the stability required for long life. Femtosecond laser has a very narrow pulse width, and the energy density after focusing is as high as 10 14 -10 15 W / cm 2 , which exceeds the Coulomb field strength of hydrogen atoms. Therefore, near the focus, even if the material itself does not have intrinsic absorption at the laser wavelength, it will achieve highly spatially selective microstructure modification and give the material unique optical functions due to nonlinear reactions such as laser-induced multiphoton absorption and multiphoton ionization. This advantage is unmatched by other laser light sources (traditional continuous and long pulse lasers).

[0003] Fluorescent silver quantum clusters, [Ag m ] x+ , is a molecular cluster composed of several to dozens of silver atoms or ions, and is also a new, efficient, multi-order femtosecond laser-induced fluorescence information carrier. [Ag m ] x+ It has a sub-nanometer size comparable to the electron Fermi wavelength, a molecular-like energy level structure determined by the quantum confinement effect and molecular-like high-efficiency fluorescence, and has low optical sensitivity suitable for low-power femtosecond laser writing. Its valence state is easier to control and the cost of raw materials is also low. Therefore, as a low-threshold fluorescence active center, it is considered to have better comprehensive performance than other precious metal quantum clusters such as copper, gold and platinum. At the same time, inorganic glass is considered to be one of the best medium material choices for femtosecond laser information storage, with very good physical and chemical stability, especially low optical sensitivity and high laser damage threshold. Due to the fluorescence [Ag m ] x+ Quantum clusters are chemically very active, so dispersing them in the glass network is also beneficial to stabilize their size distribution and fluorescence properties. + Microstructural rewriting with spatial resolution in glass, Ag+ The electrons that are susceptible to laser-induced ionization are reduced and aggregate to form fluorescent [Ag m ] x+ Quantum clusters.

[0004] Furthermore, in order to improve the femtosecond laser damage threshold of the glass matrix, reducing its linear absorption coefficient and nonlinear absorption coefficient is an effective way. Studies have shown that reducing the concentration of non-bridging oxygen, introducing fluoride components, and avoiding the use of alkali metal ions and heavy metal ions in the phosphate glass system will help reduce the sensitivity of the glass matrix to femtosecond lasers. Therefore, a low-polarizability fluorophosphate system is used to utilize the spatial selectivity of the femtosecond laser to induce the formation of [Ag m ] x+ As information carriers, quantum clusters are expected to achieve the goals of ultra-large capacity, high density and long lifetime of optical storage. m ] x+ Quantum cluster method, there is still [Ag m ] x+ The bottlenecks are that quantum clusters are easy to aggregate and grow, resulting in fluorescence inactivation and the chemical stability of fluorophosphate glass is poor.

[0005] In order to avoid [Ag m ] x+ The fluorescence inactivation caused by excessive “reduction-aggregation-growth” of quantum clusters can be solved by adopting a high oxidation / reduction potential glass system and constructing a corresponding molecular-level cage structure. On the one hand, a high oxidation / reduction potential glass system is conducive to maintaining [Ag m ] n+ The effective charge (n + ); On the other hand, constructing a molecular cage structure in glass is expected to make [Ag m ] x+ Keeping the degree of polymerization (m) low, studies have shown that there are also [P4O 10 ] cage-like molecular structural units, the ring structural units in [AlPO4] and the cage-like structural units in [Zn7(PO4)6] in zinc phosphate. Therefore, during the melting process [P4O 10 ] can be opened and reconnected into a ring or larger cage-like molecular unit, or with [Al(O,F) x ]、[Zn(O,F) z ] and other tetrahedral units are cross-linked to form a cage structure. m ] n+ The quantum clusters are embedded in these closed cage structures, which is expected to inhibit their further growth and inactivation; at the same time, [Ag m ] n+It can form relatively weak coordination bonds with the bridging oxygen on the [Al(O,F)x], [P(O,F)y][Zn(O,F)z] tetrahedrons, thus preventing it from forming a more electronegative valence bond with the non-bridging oxygen at the end of the phosphorus oxygen chain and being reduced. Summary of the invention

[0006] The present invention aims to provide a method for treating the [Ag m ] x+ The stability and uniform distribution of the glass network and the stability of the local cage structure [Ag m ] x+ , provide a femtosecond laser induced fluorescent silver quantum cluster fluorophosphate glass and a preparation method thereof.

[0007] The object of the present invention is achieved through the following technical solutions: The first aspect of the embodiment of the present invention provides a fluorescent silver quantum cluster fluorophosphate glass and a preparation method thereof, and its components and molar percentages are as follows:

[0008]

[0009] Among them, [SiO4] represents silicon-oxygen tetrahedron; [Al(O,F) x ],[P(O,F) y ],[Mg(O,F) z ] and [Zn(O,F) w ] represents a fluorine-oxygen mixed coordination polyhedron; Ag represents the silver element content; F / O represents the fluorine-oxygen atomic ratio.

[0010] A second aspect of the embodiment of the present invention provides a method for preparing the above-mentioned silver quantum cluster doped blue-green fluorescent glass, the steps of which are as follows:

[0011] (1) using SiO2, Al(PO3)3, MgF2, MgO, ZnF2, ZnO and AgNO3 powder raw materials respectively, introducing SiO2, Al2O3, P2O5, MgO (MgF2), ZnO (ZnF2) and Ag2O according to the molar percentage composition of claim 1, calculating their mass percentages and weighing each raw material in proportion;

[0012] (2) Mix SiO2, Al(PO3)3, MgO(MgF2), ZnO(ZnF2) and AgNO3 powder raw materials evenly and put them into a corundum crucible. Then, place them in an air atmosphere in a box-type electric furnace at 1450°C for melting for 45 minutes. Pour them into a mold to form a glass block. Then, place them in a box-type electric furnace at 200-400°C for 2-6 hours to anneal and remove internal stress. Then, grind and polish the glass piece into a 20 mm*20 mm*2 mm glass piece.

[0013] A third aspect of the embodiments of the present invention provides an application of fluorescent silver quantum cluster fluorophosphate glass in memory storage.

[0014] Furthermore, using 1030nm laser direct writing, a series of pulses interact with the glass to generate free electrons, which react with Ag + +e - →Ag 0 andxAg + +yAg 0 →[Ag m ] n+ , to write information in the fluorescent silver quantum cluster fluorophosphate glass. The fluorescent silver quantum cluster fluorophosphate glass after femtosecond laser is read using a 405nm laser.

[0015] Beneficial effects of the present invention: The glass of the present invention is divided into three phases: silicate phase, aluminophosphate phase and fluoride phase. (1) The low polarizability fluorophosphate system uses the spatial selectivity of femtosecond laser to induce the formation of [Ag m ] x+ As information carriers, quantum clusters are expected to achieve the goals of ultra-large capacity, high density and long life optical storage. (2) By rationally introducing negatively charged tetrahedral units such as [AlO4], [MgO4] and [ZnO4], using Ag + The ions act as charge compensators for these tetrahedra, promoting the uniform distribution of Ag+ ions. In addition, the introduction of [AlO4] and [ZnO4] can also improve the connectivity of the three-dimensional network of the glass and increase the physicochemical stability of the glass system by introducing the silicate phase; (3) In order to avoid [Ag m ] x+ The fluorescence inactivation caused by excessive "reduction-aggregation-growth" of quantum clusters is solved by adopting a high oxidation / reduction potential glass system and constructing a corresponding molecular-level cage structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is the XRD curve of multi-color silver quantum cluster doped multi-phase fluorescent glass;

[0017] Figure 2 It is the DTA spectrum of fluorosilicate phase-separated glass;

[0018] Figure 3 It is the Raman spectrum of fluoroaluminophosphosilicate phase-separated glass;

[0019] Figure 4 PL spectrum of fluoroaluminophosphosilicate glass;

[0020] Figure 5Example 5: Schematic diagram of reading with 405nm laser after writing with a single pulse of 1030nm laser energy (0.25μJ to 7.5μJ). DETAILED DESCRIPTION

[0021] The present invention is described in detail below in conjunction with the accompanying drawings. In the absence of conflict, the features of the following embodiments and implementations can be combined with each other.

[0022] The present invention proposes a fluorescent silver quantum cluster fluorophosphate glass, which stabilizes low-polymerization fluorescent [Ag m ] n+ ; (2) Increase the topological constraint value of the glass structure through the aluminum-oxygen mixed network and enhance the chemical stability of the glass; obtain a new type of Ag + / [Ag m ] n+ Optically bistable fluorophosphoaluminosilicate glass can provide a new material basis for the development of high-density information storage technology.

[0023] The present invention provides a fluorescent silver quantum cluster fluorophosphate glass, which has the following structural proportions in terms of molar percentage:

[0024]

[0025] Among them, [SiO4] represents silicon-oxygen tetrahedron; [Al(O,F) x ],[P(O,F) y ],[Mg(O,F) z ] and [Zn(O,F) w ] represents a fluorine-oxygen mixed coordination polyhedron; Ag represents the silver element content; F / O represents the fluorine-oxygen atomic ratio.

[0026] The fluorescent silver quantum cluster fluorophosphate glass provided by the present invention is prepared according to the following steps:

[0027] (1) Weigh the required mass of SiO2, Al2O3, P2O5, MgO, ZnO, MgF2, ZnF2 and Ag2O powder raw materials respectively according to the molar percentage ratio;

[0028] (2) Al(PO3)3, AgNO3, SiO2, MgO(MgF2) and ZnO(ZnF2) powder raw materials are mixed evenly and put into a corundum crucible, and then placed in a box-type electric furnace at 1300-1500°C for melting and heat preservation for 0.5-2 hours, poured into a mold to form a glass block, and then placed in a box-type electric furnace at 200-400°C for 2-6 hours for annealing to remove internal stress.

[0029] Example 1

[0030] To form the above [Al(O,F) x ],[P(O,F) y ],[Mg(O,F) z ] and [Zn(O,F) w ] and other mixed coordination polyhedra, weigh the required mass of P2O5, Al2O3, Ag2O, ZnF2 and ZnO powder raw materials respectively, the F element in ZnF2 is evenly dispersed in the glass network after forming glass and occupies the O lattice to form a mixed coordination polyhedron; mix the P2O5, Al2O3, Ag2O, ZnF2 and ZnO powder raw materials evenly and put them into a corundum crucible, in which Ag2O accounts for 3% of the total molar number of the glass components, ZnF2 and ZnO each account for 10% of the total molar number of the glass components, P2O5 and Al2O3 account for 55% and 22% respectively, and then put them into a 1450℃ box-type electric furnace for insulation melting for 45 minutes, pour them into a mold to form a glass block, place the glass block at 300℃ for insulation for 4h to remove internal stress, take out a part of them and then break them and grind them into powder for the rest of the test.

[0031] like Figure 1 to Figure 4 As shown in the figure, after measurement, the XRD of the glass shows diffuse bun peaks showing amorphous state, and DTA shows obvious Tc and Tg peaks, ΔT = 204℃, and good glass-forming properties. In the Raman spectrum, most of the phosphate skeleton has only two bridging oxygens, and the remaining two oxygens in the network structure are connected to F or other fluorine phosphorus coordination polyhedra (Zn; Al). After laser treatment, the PL laser spectrum shows good fluorescence properties, but the intensity is not optimal.

[0032] Embodiment 2:

[0033] To form the above [Al(O,F) x ],[P(O,F) y ],[Mg(O,F) z ] and [Zn(O,F) w] and other mixed coordination polyhedra, weigh the required mass of P2O5, Al2O3, Ag2O, MgF2 and MgO powder raw materials respectively. After forming glass, the F element in MgF2 is evenly dispersed in the glass network and occupies the O lattice to form a mixed coordination polyhedron. P2O5, Al2O3, Ag2O, MgF2 and MgO powder raw materials are evenly mixed and put into a corundum crucible. In this composition, Ag2O accounts for 3% of the total molar number of glass components, MgF2 and MgO each account for 10% of the total molar number of glass components, and P2O5 and Al2O3 account for 55% and 22% respectively. Then put it into a 1450℃ box-type electric furnace for heat preservation and melting for 45 minutes, pour it into a mold to form a glass block, place the glass block at 300℃ for 4h to remove internal stress, take out a part of it, then break it and grind it into powder for the rest of the test.

[0034] After measurement, the XRD of the glass showed diffuse bun peaks showing amorphous state, and DTA showed obvious Tc and Tg peaks, ΔT = 135℃, with good glass-forming properties. In the Raman spectrum, most of the phosphate skeleton has only two bridging oxygens, and the remaining two oxygens in the network structure are connected to F or other fluorine-phosphorus coordination polyhedra (Mg; Al). After laser treatment, the PL laser spectrum showed good fluorescence properties, but the intensity was not optimal, stronger than the first component in Example 1.

[0035] Embodiment 3:

[0036] To form the above [Al(O,F) x ],[P(O,F) y ],[Mg(O,F) z ] and [Zn(O,F) w ] and other mixed coordination polyhedra, weigh the required mass of P2O5, Al2O3, Ag2O, MgF2 and ZnF2 powder raw materials respectively, the F element in ZnF2 and MgF2 is evenly dispersed in the glass network after forming glass and occupies the lattice of O to form mixed coordination polyhedra; P2O5, Al2O3, Ag2O, MgF2 and ZnF2 powder raw materials are evenly mixed and put into a corundum crucible, in which Ag2O accounts for 3% of the total molar number of phase-separated fluorophosphate, MgF2 and ZnF2 each account for 10% of the total molar number of fluorophosphate, P2O5 and Al2O3 account for 55% and 22% respectively. Then put it into a 1450℃ box-type electric furnace for heat preservation and melting for 45 minutes, pour it into a mold to form a glass block, place the glass block at 300℃ for 4h to remove internal stress, take out a part of it, then break it and grind it into powder for the rest of the test.

[0037] After measurement, the XRD of the glass showed diffuse bun peaks showing amorphous state, and DTA showed obvious Tc and Tg peaks, ΔT = 121 ° C, and good glass-forming properties. In the Raman spectrum, most of the phosphate skeleton has only two bridging oxygens, and the remaining two oxygens in the network structure are connected to F or other fluorine-phosphorus coordination polyhedra (Mg; Zn; Al). After laser treatment, the PL laser spectrum showed good fluorescence properties, but the intensity was not optimal, between the components of Example 1 and Example 2.

[0038] Embodiment 4:

[0039] To form the above [Al(O,F) x ],[P(O,F) y ],[Mg(O,F) z ] and [Zn(O,F) w ] and other mixed coordination polyhedrons, and the required mass of P2O5, Al2O3, Ag2O, AlF3, MgF2 and ZnF2 powder raw materials are weighed respectively. After forming the glass, the F element in ZnF2, MgF2 and AlF3 is evenly dispersed in the glass network and occupies the O lattice site to form a mixed coordination polyhedron. The P2O5, Al2O3, Ag2O, AlF3, MgF2 and ZnF2 powder raw materials are evenly mixed and put into a corundum crucible. In this composition, Ag2O accounts for 3% of the total molar number of the glass, AlF3, MgF2 and ZnF2 account for 6%, 6% and 8% of the total molar number of the glass respectively, and P2O5 and Al2O3 account for 55% and 22% respectively. It was then placed in a 1450°C box-type electric furnace for melting and heat preservation for 45 minutes, poured into a mold for forming, and a glass block was obtained. The glass block was placed at 300°C for 4 hours to remove internal stress, a portion of it was taken out, crushed and ground into powder for the rest of the test.

[0040] After measurement, the XRD of the glass showed diffuse bun peaks showing amorphous state, and DTA showed obvious Tc and Tg peaks, ΔT = 172 ° C, with good glass-forming properties. In the Raman spectrum, most of the phosphate skeleton has only two bridging oxygens, and the remaining two oxygens in the network structure are connected to F or other fluorine-phosphorus coordination polyhedra (Mg; Zn; Al). After laser treatment, the PL laser spectrum showed good fluorescence properties, with the best fluorescence intensity.

[0041] Embodiment 5:

[0042] To form the above [Al(O,F) x ],[P(O,F) y ],[Mg(O,F) z ] and [Zn(O,F) w] and other mixed coordination polyhedrons, and the required masses of SiO2, P2O5, Al2O3, Ag2O, AlF3, MgF2 and ZnF2 powder raw materials are weighed respectively. After forming the glass, the F element in ZnF2, MgF2 and AlF3 is evenly dispersed in the glass network and occupies the O lattice site to form a mixed coordination polyhedron; the SiO2, P2O5, Al2O3, Ag2O, AlF3, MgF2 and ZnF2 powder raw materials are evenly mixed and put into a corundum crucible. In this composition, Ag2O accounts for 3% of the total molar number of the glass, AlF3, MgF2 and ZnF2 account for 6%, 6% and 8% of the total molar number of the glass respectively, and SiO2, P2O5 and Al2O3 account for 10%, 48% and 19% respectively. It was then placed in a 1450°C box-type electric furnace for melting and heat preservation for 45 minutes, poured into a mold for forming, and a glass block was obtained. The glass block was placed at 300°C for 4 hours to remove internal stress, a portion of it was taken out, crushed and ground into powder for the rest of the test.

[0043] After measurement, the XRD of the glass showed diffuse bun peaks showing amorphous state, and DTA showed obvious Tc and Tg peaks, ΔT = 203℃, with the best glass-forming performance. In the Raman spectrum, most of the phosphate skeleton has only two bridging oxygens, and the remaining two oxygens in the network structure are connected to F or other fluorine-phosphorus coordination polyhedra (Mg; Zn; Al), and the silicate phase separates the phosphate phase in the glass structure.

[0044] The present invention provides an application of fluorescent silver quantum cluster fluorophosphate glass in memory storage. Using 1030nm laser direct writing, a series of pulses interact with the glass to generate free electrons, which react with Ag + +e - →Ag 0 andxAg + +yAg 0 →[Ag m ] n+ , to write information in the fluorescent silver quantum cluster fluorophosphate glass. Then use 405nm laser to read the fluorescent silver quantum cluster fluorophosphate glass after femtosecond laser.

[0045] The glass prepared in Example 5 was treated with 1030nm laser direct writing. After laser treatment, the PL laser spectrum showed good fluorescence performance, and the fluorescence intensity was the second strongest. Figure 5 The schematic diagram is read under 405nm laser, and the engraved information is clear and stable.

[0046] The above embodiments are only used to illustrate the design ideas and features of the present invention, and their purpose is to enable those skilled in the art to understand the content of the present invention and implement it accordingly. The protection scope of the present invention is not limited to the above embodiments. Therefore, any equivalent changes or modifications made based on the principles and design ideas disclosed by the present invention are within the protection scope of the present invention.

Claims

1. A fluorescent silver quantum cluster fluorophosphate glass, characterized in that: In terms of mole percentage, it has the following structural ratios: [SiO4] 10%~20% <h2 style=";text-align:left;direction:ltr">[Al(O,F)<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> ], (4≤x≤6) 20~25% [P(O,F) y ], (4≤y≤6) 40~50% [Mg(O,F) z ], (4≤z≤6) 0~14% [Zn(O,F) w ], (4≤w≤6) 0~14% Ag 1~5% F / O 4~10% Among them, [SiO4] represents silicon-oxygen tetrahedron; [Al(O,F) x ], [P(O,F) y ], [Mg(O,F) z ] and [Zn(O,F) w ] represents a fluorine-oxygen mixed coordination polyhedron; Ag represents the silver element content; F / O represents the fluorine-oxygen atomic ratio.

2. A method for preparing a fluorescent silver quantum cluster fluorophosphate glass according to claim 1, characterized in that: The following steps are involved: (1) Weigh the required mass of SiO2, Al2O3, Al(PO3)3, MgO, ZnO, MgF2, ZnF2 and AgNO3 powder raw materials respectively according to the molar percentage ratio; (2) Al(PO3)3, Al2O3, AgNO3, SiO2, MgO, MgF2 and ZnO, ZnF2 powder raw materials are mixed evenly and put into a corundum crucible, and then placed in a 1300~1500 °C box-type electric furnace for insulation melting for 0.5~2 hours, poured into a mold to form a glass block, and then placed in a 200~400 °C box-type electric furnace for insulation for 2~6 hours to anneal and remove internal stress.

3. An application of the fluorescent silver quantum cluster fluorophosphate glass according to claim 1 in memory storage.

4. The use according to claim 3, characterized in that: include: Using 1030nm laser direct writing, a series of pulses interact with the glass to generate free electrons, which react with Ag + +e - →Ag 0 andxAg + +yAg 0 →[Ag m ] n+ , to write information in fluorescent silver quantum cluster fluorophosphate glass.

5. The use according to claim 3 or 4, characterized in that: include: The fluorescent silver quantum cluster fluorophosphate glass after femtosecond laser was read using a 405nm laser.

Citation Information

Patent Citations

  • Multicolor silver quantum cluster doped multiphase fluorescent glass and preparation method thereof

    CN111018348A